2017
DOI: 10.1002/ep.12849
|View full text |Cite
|
Sign up to set email alerts
|

Zero valent iron loaded on SiC nanoparticles as a new adsorbent for removing Pb (lead) and azo dyes from aqueous solution

Abstract: A reusable silicon carbide nanoparticle supported by nano zero‐valent iron (nZVI) is prepared by a simple precipitation method. The results of thermal gravimetric analysis (TGA), dynamic light scattering (DLS), vibrating‐sample magnetometer (VSM), Fourier transform infrared spectroscopy (FT‐IR), transmission electron microscopy (TEM), scanning electron microscopy with X‐ray microanalysis (SEM‐EDS), X‐ray powder diffraction, and N2 adsorption isotherms indicated that the zero‐valent iron was successfully deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…From Table 3, it is observed that the correlation of determination R 2 value of Langmuir isotherm model (R 2 = 0.806) is favorable to the experimental data than Freundlich isotherm model (R 2 = 0.657). This demonstrates that the monolayer physical adsorption of dye molecules on the homogenous nano iron particles was achieved [66]. An indication of degree of the molecular interactions in the adsorbed phase is provided by a parameter called the separation factor R L , which is used to describe the essential characteristics of Langmuir isotherm.…”
Section: Adsorption Isothermmentioning
confidence: 86%
“…From Table 3, it is observed that the correlation of determination R 2 value of Langmuir isotherm model (R 2 = 0.806) is favorable to the experimental data than Freundlich isotherm model (R 2 = 0.657). This demonstrates that the monolayer physical adsorption of dye molecules on the homogenous nano iron particles was achieved [66]. An indication of degree of the molecular interactions in the adsorbed phase is provided by a parameter called the separation factor R L , which is used to describe the essential characteristics of Langmuir isotherm.…”
Section: Adsorption Isothermmentioning
confidence: 86%